Transcriptome Analysis of Atlantic Salmon (Salmo salar) Skin in Response to Sea Lice and Infectious Salmon Anemia Virus Co-Infection Under Different Experimental Functional Diets - Cai, Wenlong; Kumar, Surendra; Navaneethaiyer, Umasuthan; Caballero-Solares, Albert; Carvalho, Laura A.; Whyte, Shona K.; Purcell, Sara L.; Gagne, Nellie; Hori, Tiago S.; Allen, Melissa; Taylor, Richard G.; Balder, Rachel; et al. (Frontiers in Immunology, 2022)
Sea lice (Lepeophtheirus salmonis) are ectoparasitic copepods that cause significant economic loss in marine salmoniculture. In commercial salmon farms, infestation with sea lice can enhance susceptibility to other significant pathogens, such as the highly contagious infectious salmon anemia virus (ISAv). In this study, transcriptomic analysis was used to evaluate the impact of four experimental functional feeds (i.e. 0.3% EPA/DHA+high-ω6, 0.3% EPA/DHA+high-ω6+immunostimulant (IS), 1% EPA/DHA+high-ω6, and 1% EPA/DHA+high-ω3) on Atlantic salmon (Salmo salar) during a single infection with sea lice (L. salmonis) and a co-infection with sea lice and ISAv. The overall objectives were to compare the transcriptomic profiles of skin between lice infection alone with co-infection groups and assess differences in gene expression response among animals with different experimental diets. Atlantic salmon smolts were challenged with L. salmonis following a 28-day feeding trial. Fish were then challenged with ISAv at 18 days post-sea lice infection (dpi), and maintained on individual diets, to establish a co-infection model. Skin tissues sampled at 33 dpi were subjected to RNA-seq analysis. The co-infection’s overall survival rates were between 37%-50%, while no mortality was observed in the single infection with lice. We identified 756 and 1303 differentially expressed genes (DEGs) in “lice infection vs. pre-infection” and “co-infection vs. pre-infection” groups, respectively, that were shared between the four experimental diets. The co-infection groups (co-infection vs. pre-infection) included up-regulated genes associated with wound healing, the interferon pathway, complement cascade activity, and heat shock protein family, while the down-regulated genes were related to antigen presentation and processing, T-cell activation, collagen formation, and extracellular matrix. Pathway enrichment analysis conducted between infected groups (lice infection vs. co-infection) resulted in several immune-related significant GO terms and pathways unique to this group, such as “autophagosome”, “cytosolic DNA-sensing pathway” and “response to type 1 interferons”. Understanding how experimental functional feeds can impact the host response and the trajectory of co-infections will be an essential step in identifying efficacious intervention strategies that account for the complexities of disease in open cage culture.